Satisfaction Regarding Hospital Orientation among Staff Nurses in a Selected Hospital, Bengaluru. (International Journal of Scientific Research and Management (IJSRM), 2017)
Satisfaction has become increasingly popular as a critical component in the orientation programme. Though orientation programmes are sequenced and well scheduled in theory and curriculum, practice lacks the sequence and implementation due to various reasons. The study aimed to determine the level of satisfaction regarding hospital orientation among staff nurses in a selected hospital using a quantitative survey approach with a descriptive research design. A consented sample of 100 staff nurses were enrolled in the study using a purposive sampling technique based on inclusion and exclusion criteria. Data was collected using a researcher developed Self administered nurse Orientation Rating Scale, including a demographic profile and an opinionnaire in the wards and hostel premises attached to the hospital. Data was pooled and analyzed using descriptive and inferential statistics. The findings of the study reveal that 98% of the study subjects were satisfied with the hospital orientation, while 2% were partially satisfied and none of the staff nurses reported dissatisfaction.The computed chi-square/fisher exact test values show no significant (p>0.05) association between sample characteristics and level of satisfaction regarding hospital orientation.